J14 Subcutaneous haloperidol for chorea in patients with Huntington's disease and dysphagia. (12th September 2022) - Lee, Sarah CM; Jayasinghe, Indrajith; Lie, Yenni
Abstract : In Huntington's Disease (HD), severe dysphagia can impede oral intake of medication, including medications for chorea. Here we describe how this was managed in our neuro-palliative inpatient unit. A 40 year old female had advanced disease with difficult to control chorea, severe dysphagia, marked cognitive impairment and spent most of her day in HD bed or chair. In the last year she was unable to communicate verbally and was generally drowsy. She was on oral tetrabenazine, risperidone, mirtazapine, escitalopram and valproate. She presented to ED with aspiration pneumonia, spending two days nil by mouth, receiving IV antibiotics and IV valproate. On arrival to our unit, she was cachectic, non-communicative, had bleeding skin abrasions on her face, body and limbs from almost constant 'violent chorea', and had minimal, inconsistent oral intake. We converted the oral risperidone to haloperidol sub-cutaneous injection with good effect. As her chorea and dysphagia improved, haloperidol was converted to an oral dose and she was restarted on her other oral medication. Due to ongoing sedation and excellent control of chorea, tetrabenazine was weaned off. Subcutaneous haloperidol is well established in palliative care and has the benefits of high bioavailability, quick action, minimal local irritation, and is relatively safe. Subcutaneous haloperidol is a good option for managing chorea in patients who are unable to swallow. Although used as a palliative measure, the benefits are such that we think this should be considered an option for rescue treatment in HD.